Comparative Evaluation of Single-lap Joints Bonded with Different Adhesives by Cohesive Zone Modelling. (2015) - Campilho, R.D.S.G.; Fernandes, T.A.B.
Abstract: Structures built from several components require some means of joining. In this context, bonding with adhesives has several advantagescompared to traditional joining methods, e.g. reduction of stress concentrations, reduced weight penalty and easy manufacturing. Adhesives can be strong and brittle (e.g., Araldite ® AV138) or less strong and ductile (e.g., Araldite ® 2015). A new family of polyurethane adhesives combines high strength and ductility (e.g., Sikaforce ® 7888). In this work, the performance of the three above mentioned adhesives was tested in single-lap joints with varying values of overlap length ( L O ). The experimental work carried out is accompanied by a detailed numerical analysis by Finite Elements, based on Cohesive Zone Models (CZM). This procedure enabled detailing the performance of this predictive technique applied to bonded joints. Moreover, it was possible to evaluate which family of adhesives is more suited for each joint geometry. CZM revealed to be highly accurate, except for largely ductile adhesives, although this could be circumvented with a different cohesive law.